Differential Regulation of Stomatal Conductance as a Strategy to Cope With Ammonium Fertilizer Under Ambient Versus Elevated CO2 - Torralbo, Fernando; González-Moro, María Begoña; Baroja-Fernández, Edurne; Aranjuelo, Iker; González-Murua, Carmen (Frontiers in Plant Science, 2019)
While nitrogen (N) derived from ammonium would be energetically less expensive than nitrate-derived N, the use of ammonium-based fertilizer is limited by the potential for toxicity symptoms. Nevertheless, previous studies have shown that exposure to elevated CO2 favors ammonium assimilation in plants. However, little is known about the impact of different forms of N fertilizer on stomatal opening and their consequent effects on CO2 and H2O diffusion in wheat plants exposed to ambient and elevated CO2. In this paper we have examined the response of the photosynthetic machinery of durum wheat (Triticum durum, var. Amilcar) grown with different types of N fertilizer (NO3-, NH4+ and NH4NO3) at 400 versus 700 ppm of CO2. Alongside gas exchange and photochemical parameters, the expression of genes involved in CO2 (PIP1.1 and PIP2.3) and H2O (TIP1) diffusion as well as key C and N primary metabolism enzymes and metabolites were studied. Our results show that at 400 ppm CO2, wheat plants fertilized with ammonium as the N source had oxidative stress symptoms and a strong reduction in stomatal conductance, which negatively affected photosynthetic rates. The higher levels of PIP1.1 and PIP 2.3 expression in ammonium-fertilized plants at 400 ppm CO2 might reflect the need to overcome limitations to the CO2 supply to chloroplasts due to restrictions in stomatal conductance. This stomatal limitation might be associated with a strategy to reduce ammonium transport toward leaves. On the other hand, ammonium-fertilized plants at elevated CO2 did not show stress symptoms and no differences were detected in stomatal opening or water use efficiency (WUE). Moreover, similar gene expression of the aquaporins TIP1, PIP1.1 and PIP2.3 in ammonium-fertilized plants grown at 700 ppm compared to nitrate- and ammonium nitrate-plants would suggest that an adjustment in CO2 and H2O diffusion is not required. Therefore, in the absence of a stress context triggered by elevated CO2, ammonium- and ammonium nitrate-fertilized plants were able to increase their photosynthetic rates, which was translated eventually into higher leaf protein content.